2022
DOI: 10.3389/fendo.2022.983723
|View full text |Cite
|
Sign up to set email alerts
|

Role of advanced glycation end products on vascular smooth muscle cells under diabetic atherosclerosis

Abstract: Atherosclerosis (AS) is a chronic inflammatory disease and leading cause of cardiovascular diseases. The progression of AS is a multi-step process leading to high morbidity and mortality. Hyperglycemia, dyslipidemia, advanced glycation end products (AGEs), inflammation and insulin resistance which strictly involved in diabetes are closely related to the pathogenesis of AS. A growing number of studies have linked AGEs to AS. As one of the risk factors of cardiac metabolic diseases, dysfunction of VSMCs plays an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 223 publications
0
10
0
Order By: Relevance
“…[129][130][131][132][133] AGEs are typically produced during the aging process, though excessive production of AGEs is associated with vascular inflammation, atherosclerosis, OS, insulin resistance, and diabetes. [134] AGEs promote the release of pro-inflammatory cytokines in diabetes and other metabolic disorders. [134] AGEs induce the propagation of OS and inflammatory disorders in diabetes with subsequent activation of the Nrf2 pathway to reduce OS and/or inflammatory reactions.…”
Section: Nrf2 Role In Inflammation and Immune Responsementioning
confidence: 99%
See 2 more Smart Citations
“…[129][130][131][132][133] AGEs are typically produced during the aging process, though excessive production of AGEs is associated with vascular inflammation, atherosclerosis, OS, insulin resistance, and diabetes. [134] AGEs promote the release of pro-inflammatory cytokines in diabetes and other metabolic disorders. [134] AGEs induce the propagation of OS and inflammatory disorders in diabetes with subsequent activation of the Nrf2 pathway to reduce OS and/or inflammatory reactions.…”
Section: Nrf2 Role In Inflammation and Immune Responsementioning
confidence: 99%
“…[134] AGEs promote the release of pro-inflammatory cytokines in diabetes and other metabolic disorders. [134] AGEs induce the propagation of OS and inflammatory disorders in diabetes with subsequent activation of the Nrf2 pathway to reduce OS and/or inflammatory reactions. [135] Indeed, Nrf2/HO-1/NQO1 axis is highly activated in the endothelial cells subjected to AGEs activators to provide an adaptive response against OS and/or inflammatory reactions in diabetes.…”
Section: Nrf2 Role In Inflammation and Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Given that AGEs are able to induce the proliferation of various types of cells [19,[25][26][27], we speculated that increased AGEs could contribute to the excessive proliferation of epidermal keratinocytes in psoriasis. To verify this, we first examined the growth of NHKs treated with BSA-AGEs via CCK8 assay and resazurin-reduction assay.…”
Section: Ages Promote the Proliferation Of Keratinocytes Via Upregula...mentioning
confidence: 99%
“…Hyperinsulinemia, which is caused by IR, is a potential growth factor that promotes its growth through the MAPK pathway, which catalyzes the phosphorylation of transcription factors that stimulate VSMCs growth, proliferation, and differentiation ( 52 ). It has been demonstrated that IR-related inflammation can also promote the development of VSMCs ( 53 ). C-peptide, produced by the cleavage of proinsulin in the β-cell.…”
Section: Introductionmentioning
confidence: 99%